Meningkatkan Kapasitas Guru dalam Pembuatan Konten Edukasi Digital melalui Program KKN di SDIT UMMI Kota Bengkulu - Revola, Yashori; Amelia, Tri Puja; Alfaiza, Lolla; Sari, Maiya Linda; Absya, Bafelia Indriyati; Naurahlatifa, Nadiahhanun Wennya; Puspitasari, Desti; Zahra, Karin; Nurkhasanah, Siti; Andini, Fitri; Candra, Naurah Crisandini Putri; Putri, Dini Agestia; Rahmatullah, Farhan Melsi; Nugraha, Bayu; Harafilo, Sindra Pikrin (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata or KKN) is a form of student engagement aimed at providing tangible contributions to societal challenges, particularly in the field of education. The KKN program implemented at SD IT UMMI Kota Bengkulu focused on enhancing teachers’ capacity in creating digital educational content. This initiative was driven by the growing demand for technology integration in learning and the need for teachers to develop digital skills to produce engaging and effective teaching media. Through a series of workshops and mentoring sessions utilizing applications such as Canva and CapCut, teachers were guided in designing and producing interactive and contextual learning materials. The outcomes of the program indicated a significant improvement in teachers’ ability to independently create digital presentations and educational videos. This program had a positive impact on the quality of teaching at the school and serves as a model for collaboration between higher education institutions and primary schools in strengthening educational human resources.